Benzoic and salicylic acid are the signaling molecules of Chlorella cells for improving cell growth. (February 2021) - Fu, Liang; Li, Qingcheng; Chen, Congli; Zhang, Yueju; Liu, Yinglu; Xu, Liang; Zhou, Yihan; Li, Chengbin; Zhou, Dandan; Rittmann, Bruce E.
Abstract: Cell-to-cell communication regulates microalgae production via signaling molecules (SMs), but few microalgal SM species are known. Here, we document two new microalgae SMs, benzoic acid (BA) and salicylic acid (SA). Initially, crude SMs were extracted from a microalgae culture in which microalgae grew on heterotrophic-enriched phosphorus nutrition. The extracted SMs enhanced Chlorella growth by ∼72%, promoted nutrient uptake, and up-regulated the mitogen-activated protein-kinase signaling cascade. Fourier transform infrared and nuclear magnetic resonance analyses identified the putative SMs was aromatic carboxylic acids. BA and SA were identified using high-resolution mass spectrometry. BA and SA addition increased cell growth by ∼75% and ∼25%; and improved ATP production by ∼35% and ∼20%. Transcriptomic analysis showed that BA and SA were biosynthesized via CoA-dependent, non-oxidative pathway. The SMs upregulated TCA-cycle enzymes, which promoted carbon assimilation and activated DNA-replicating enzyme, so that accelerated cell division. This study identified two new SMs for microalgae cell communication and provides means to identify other SMs. Graphical abstract: Image 1 Highlights: Luxury phosphorous promoted plant hormones production. Benzoic acid (BA) and salicylic acid (SA) were newly endogenous signaling molecules. BA and SA enhanced Chlorella growth and improved ATP production. Signaling molecules upregulated TCA cycle, carbon assimilation and DNA replication.